Increased Severe Cases and New-Onset Type 1 Diabetes Among Children Presenting With Diabetic Ketoacidosis During First Year of COVID-19 Pandemic in Turkey - Kiral, Eylem; Kirel, Birgul; Havan, Merve; Keskin, Mehmet; Karaoglan, Murat; Yildirim, Ahmet; Dinleyici, Ener Cagri (Frontiers Media SA, 2022)
IntroductionThere have been some significant changes regarding healthcare utilization during the COVID-19 pandemic. Majority of the reports about the impact of the COVID-19 pandemic on diabetes care are from the first wave of the pandemic. We aim to evaluate the potential effects of the COVID-19 pandemic on the severity of diabetic ketoacidosis (DKA) and new onset Type 1 diabetes presenting with DKA, and also evaluate children with DKA and acute COVID-19 infection. MethodsThis is a retrospective multi-center study among 997 children and adolescents with type 1 diabetes who were admitted with DKA to 27 pediatric intensive care units in Turkey between the first year of pandemic and pre-pandemic year. ResultsThe percentage of children with new-onset Type 1 diabetes presenting with DKA was higher during the COVID-19 pandemic (p < 0.0001). The incidence of severe DKA was also higher during the COVID-19 pandemic (p < 0.0001) and also higher among children with new onset Type 1 diabetes (p < 0.0001). HbA1c levels, duration of insulin infusion, and length of PICU stay were significantly higher/longer during the pandemic period. Eleven patients tested positive for SARS-CoV-2, eight were positive for new onset Type 1 diabetes, and nine tested positive for severe DKA at admission. DiscussionThe frequency of new onset of Type 1 diabetes and severe cases among children with DKA during the first year of the COVID-19 pandemic. Furthermore, the cause of the increased severe presentation might be related to restrictions related to the pandemic; however, need to evaluate the potential effects of SARS-CoV-2 on the increased percentage of new onset Type 1 diabetes.
Ülgen Tekerek, Nazan/0000-0002-4577-1488; Havan, Merve/0000-0003-3431-7906; Akçay, Nihal/0000-0002-8273-2226; Bozan, Gürkan/0000-0001-5041-8892; Kahveci, Fevzi/0000-0002-5176-1040; Ozcifci, Gokcen/0000-0001-5245-9786; Soydan, Ekin/0000-0003-2626-5499; Guven, Ayla/0000-0002-2026-1326; Ozturk, Zeynelabidin/0000-0001-8548-4144; Akçay, Nihal/0000-0002-8273-2226; Kaya, Gülay/0000-0002-0713-5122; Yazıcı Özkaya, Pınar/0000-0002-1209-2534; Altuğ, Ümüt/0000-0002-6864-377X; Koçoğlu Barlas, Ülkem/0000-0001-7445-5858; Uysal Yazıcı, Mutlu/0000-0001-7377-4718; Dursun, Oguz/0000-0001-5482-3780; Yilmaz, Resul/0000-0001-7672-8100; Tekguc, Hakan/0000-0001-6424-6761; Yetimakman, Ayse Filiz/0000-0002-9334-4464; Duyu, Muhterem/0000-0001-7892-2927; Karaoglan, Murat/0000-0002-2861-3568;
Keywords: COVID-19; Children; Diabetes; Diabetic Ketoacidosis; Pandemic; Pediatric Intensive Care Unit